Abundance of soil microbes, endophytic fungi and blast disease of paddy rice with three pest management practices - suryo wiyono; Bonjok Istiaji; Hermanu Triwidodo; andika septiana suryaningsih (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wiyono S, Istiaji B, Triwidodo H, Suryaningsih AS. 2020. Abundance of soil microbes, endophytic fungi and blast disease of paddy rice with three pest management practices. Biodiversitas 21: 4234-4239. Rice production in Indonesia faces a potential threat of pests and diseases. Biointensive Integrated Pest Management (Bio IPM) is a new approach based on natural and biological control, which effectively controls pests and diseases. However, the impact of this technology on soil microbes and endophytic fungi is almost unknown. The objective of the study was to investigate the effect of Bio IPM on abundance of soil microbes, endophytic fungi, and blast disease under field conditions. Three pest management types were tested i.e. conventional, reduced pesticides, and Bio IPM. Field experiment was set in four replications in randomized complete block design. Experiments were carried out in two seasons i.e. dry and wet season. Variables assessed during experiment were amount of soil bacteria, soil fungi, phosphate solubilizing bacteria, colonization of total leaf endophytes, colonization of Nigrospora sp., and blast disease severity. The results showed that the abundance of soil bacteria and phosphate solubilizing bacteria were significantly increased with Bio IPM whereas it was not found to be significant in soil fungi. Total endophytic fungi and Nigrospora sp. were found higher in Bio IPM especially in early growth stages. Bio IPM controlled neck blast more effectively than conventional and reduced pesticides, but it did not show any significant effect on leaf blast disease.